47‐2: A Calibrated Simulation of Electroluminescent QD‐LEDs. Issue 1 (29th May 2019) - Dimmock, James A. R.; Boardman, Edward A.; Smeeton, Tim M.
Abstract : We present charge transport simulations for electroluminescent quantum dot LEDs (QD‐LEDs). The simulations operate by propagating carriers between sites via hopping, with a frequency determined from experimental mobility values. Excellent agreement with experiments is observed for devices with various layer structures. The results provide insight into charge transport in QD‐LEDs.